EFFECTIVENESS OF MARKETING ABILITY ON CONSUMER PROTECTION AND THE ROLE OF MAKING DECISION AS A MEDIATOR - Salman abed Hadi; Basim Hanoon Jasim (Journal Park Publishing, 2024)
Marketing Ability (MA) is considered essential by determining its impact on Consumer Protection (CP), and this works to develop the performance of institutions, as well as focusing on the role of Making Decision (MD) by employees in the company, and this variable is considered a mediator. In this study, Marketing Ability (MA) is considered a dependent factor, and one of the basics that the researcher concluded in this study is that the productivity of organizations must be improved and their entry into the world of competition among themselves. The dependent factor, which is Consumer Protection (CP), is considered a dependent factor that emphasizes the provision of basic services to consumers, including working employees. The researcher also emphasized the Making Decision (MD) process by employees in organizations, and this is considered as a mediator factor. These results were obtained by the researcher after great efforts through follow-up and using the questionnaire form and distributing it to the employees of the Maysan Oil Company/Iraq. Was obtained positive results that helped support this study. The questionnaire form (140), the number of incorrect forms (5), the statistical analysis of data and information that the researcher used SPSS & SmartPLS 4, the Likert scale (7) and the number of theories (3) were positive.
Keywords: Marketing ability, Consumer protection, Making decision, Employee, Organization.